Community education for the oregano and damiana entrepreneurship in the community of Camargo - Velázquez-Hernández, Jorge Arturo (2023)
Training makes it possible to appropriate knowledge and thus behaviors of people and organizations to enhance their capacities for economic and human development. Therefore, a training proposal was made regarding the use and commercialization of oregano and damiana in the Camargo Community, in the Peñamiller municipality of Queretaro during the year 2022 in which, a focus group showed interest and participation, awareness, knowledge that allow them to open up individual and collective possibilities. Peñamiller is an area whose challenge is to open employment options for its inhabitants and the use of its natural resources. The linking of institutions, experts and wills, with the socialization of knowledge in sustainable rural entrepreneurship, allowed in a consensual way to achieve the implementation of this social intervention.